Formation of LiNi0.5Co0.5VO4 nano-crystals by solvothermal reaction - Thongtem T. (2014)
LiNi0.5Co0.5VO4 nano-crystals were solvothermally prepared using a mixture of LiOH·H2O, Ni(NO3)2·6H2O, Co(NO3)2·6H2O and NH4VO3 in isopropanol at 150-200 °C followed by 300-600 °C calcination to form powders. TGA curves of the solvothermal products show weight losses due to evaporation and decomposition processes. The purified products seem to form at 500 °C and above. The products analyzed by XRD, selected area electron diffraction (SAED), energy dispersive X-ray (EDX) and atomic absorption spectrophotometer (AAS) correspond to LiNi0.5Co0.5VO4. V-O stretching vibrations of VO4 tetrahedrons analyzed using FTIR and Raman spectrometer are in the range of 620-900 cm-1. A solvothermal reaction at 150 °C for 10 h followed by calcination at 600 °C for 6 h yields crystals with lattice parameter of 0.8252 ± 0.0008 nm. Transmission electron microscope (TEM) images clearly show that the solvothermal temperatures play a more important role in the size formation than the reaction times. © 2006 Elsevier Ltd and Techna Group S.r.l.